SUSTAINABLE ISLAMIC ARCHITECTURE IN SETTLEMENTS AND THEIR ENVIRONMENT IN SURAKARTA - Widyastuti Nurjayanti; Fadhilla Tri Nugrahaini (Journal of Islamic Architecture, 2023)
Islamic architecture is a science that combines architecture and Islam based on the Qur'an and Hadith. It is a built environment based on or applying Islamic basic principles and values, while sustainable architecture is a solution to save the Earth from destruction. Sustainable Islamic architecture is essential and exciting to study for some reasons. Basically, Islamic principles are compatible with sustainable architecture and green building principles. This study aims to determine old and new housings dealing with (1) sustainability through the architectural GBCI table, (2) Islamic architecture through the parameters of Islamic architecture, (3) relationship between sustainable and Islamic architecture. It was conducted using qualitative and quantitative methods based on the Greenship house table version 0.1 and Islamic architecture criteria. Analysis and discussion were carried out according to the research objectives. The study results show Islamic and sustainable architecture in old and new housing. The relationship reinforces each other, synergizes, and shows a positive correlation. It can be seen in the suitability of activities, benefits, and design implementation.